O design pedagógico para um curso de português como língua adicional para fins acadêmicos - Andrighetti, Graziela Hoerbe (2020)
Considering a perspective of social usage of language, which always occurs in a dialogical and situated way, and understanding literate practices as culturally situated social constructions, this research presents a pedagogical design proposal for the teaching of Portuguese as Additional Language for academic purposes that seeks to provide students with increased possibilities to deal with the diversity of texts that are found in the academic sphere. In order to do so, I analyzed a didactic script designed for a course aimed at working with academic genres, which is offered to undergraduate and graduate students doing an exchange program at a state university in the south of Brazil, and a course aimed at teaching academic reading and writing, offered to graduate exchange students at a private university also located in the south of Brazil. In these analyses, the purpose was to verify how these courses promoted the work with academic texts through a social perspective of language use, providing a reading and writing work that met what the students needed to do in their university routines. Based on the analysis, it is possible to state that the design of an PAL course for academic purposes committed to assisting students in their academic demands needs to consider the diversity of texts that are presented to students in the activities in which they are inserted in the academic world, considering the singularities of the conditions of production of these texts and also observing the specific ways that are established to deal with such texts. Furthermore, since Portuguese is an additional language for these students, the peculiarities of using the mother tongue and the additional language need to be considered in the texts they produce in Portuguese, bringing to the discussion sensitive perceptions not only regarding the code, but also the ways of doing things in these languages, especially regarding the academic sphere.